Disengagement in the Digital Era: Unpacking the Mediating Role of Technostress Between Job Insecurity, Digital Workload, Boreout, and Digital Presenteeism - Nora Damayanti; Ramadhi Ramadhi; Edo Andrefson (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2026)
Purpose: This study examines how digital workload and job insecurity affect employee disengagement—operationalized as boreout and digital presenteeism—by assessing technostress as a mediating mechanism in digital-intensive workplaces.Method: A quantitative, correlational survey design was employed. Data were collected from 421 employees across multiple industries using voluntary sampling. The proposed direct and indirect relationships among digital stressors, technostress, and disengagement outcomes were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM).Result: Digital workload significantly increased technostress, whereas job insecurity emerged as a strong predictor of digital presenteeism. Technostress had a significant positive effect on boreout but did not significantly predict digital presenteeism. Mediation analysis showed that technostress did not mediate the relationship between digital workload and boreout; however, digital workload exerted an indirect effect on digital presenteeism via technostress.Practical Implications for Economic Growth and Development: By elucidating how digital stressors undermine employee engagement and productivity, this study provides evidence-based guidance for designing healthier digital work systems. Interventions aimed at reducing technostress, optimizing digital workload, and mitigating job insecurity may enhance workforce efficiency, strengthen organizational performance, and support broader economic growth in digitally transforming economies.Originality/Value: The study demonstrates that distinct digital stressors produce different forms of disengagement: digital workload is more strongly associated with boreout, whereas job insecurity is more closely linked to digital presenteeism, with technostress functioning as a selective mediating pathway.